1994
DOI: 10.1172/jci116957
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of novel beta cardiac myosin heavy chain gene mutations that cause familial hypertrophic cardiomyopathy.

Abstract: Three novel 63 cardiac myosin heavy chain (MHC) gene missense mutations, Phe513Cys, Gly716Arg, and Arg719Trp, which cause familial hypertrophic cardiomyopathy (FHC) are described. One mutation in exon 15 (Phe513Cys) does not alter the charge of the encoded amino acid, and affected family members have a near normal life expectancy. The Gly716Arg mutation (exon 19; charge change of +1) causes FHC in three family members, one of whom underwent transplantation for heart failure. The Arg719Trp mutation (exon 19; ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
1
9

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(158 citation statements)
references
References 24 publications
3
145
1
9
Order By: Relevance
“…Initially, these 8 particular mutations appeared to confer a benign clinical phenotype (ie, near-normal life expectancy) based on a limited number of families: 1 large family with G256E, 12 1 family with F513C, 10 4 families with V606M, 13,14 1 family with R719Q, 15 and 1 family with L908V 19 in MYH7. The S179F-TNNT2 mutation has been reported in a single family, 16 and 3 families were evaluated for the D175N-TPM1 mutation.…”
Section: Malignant Versus Benign Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, these 8 particular mutations appeared to confer a benign clinical phenotype (ie, near-normal life expectancy) based on a limited number of families: 1 large family with G256E, 12 1 family with F513C, 10 4 families with V606M, 13,14 1 family with R719Q, 15 and 1 family with L908V 19 in MYH7. The S179F-TNNT2 mutation has been reported in a single family, 16 and 3 families were evaluated for the D175N-TPM1 mutation.…”
Section: Malignant Versus Benign Mutationsmentioning
confidence: 99%
“…10,13 Previously, we failed to identify a single patient with R719W. 28 In contrast to R719W, R719Q has been associated with nearnormal survival.…”
Section: Malignant Versus Benign Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 80 unique mutations have been reported that alter one amino acid residue in the globular head or head-rod junction of the b-myosin heavy chain. These mutations are expressed with a high degree of penetrance and most affected individuals ( ~ 90%) exhibit significant myocardial hypertrophy on two-dimensional echocardiography studies by age 20 years [16] (Fig 2A). Despite nearly complete disease penetrance and significant hypertrophy, survival in HCM caused by a β-cardiac myosin heavy chain mutation varies considerably and is, in part, mutation-specific.…”
Section: Hypertrophic Cardiomyopathy: the Clinical Diseasementioning
confidence: 99%
“…Genotype/phenotype correlation studies have been insightful, leading to the observation that FHCM seldom develops before puberty. [1][2][3][4] There are also certain age-dependent trends observed for specific genes. Myosin heavy chain mutations tend to be associated with a high incidence of sudden death, onset in the second and third decades of life, 90% to 100% penetrance, and significant hypertrophy.…”
Section: See P 2992mentioning
confidence: 99%